SDG14 assessment of progress against sustaining life below water: a case study from Torres Strait - Éva Plagányi; Nicole Murphy; Roy Aijun Deng; Laura K. Blamey; Stephanie Brodie; Leo X. C. Dutra; Steven Edgar; Denham Parker; Kinam Salee; Mark Tonks; Sharon A. Appleyard (Reviews in Fish Biology and Fisheries, 2026)

Crystal defects drive gold remobilisation in arsenopyrite - Denis Fougerouse; Nicolas Thebaud; David W. Saxey; William D.A. Rickard; Laura Petrella; Siyu Hu; Tommaso Tacchetto; Laure Martin; Wess Edgar; Steven M. Reddy (Geochimica et Cosmochimica Acta, 2026)

Trends in nematocyst abundance provide a mechanism for venom metering in the ‘upside-down’ jellyfish Cassiopea (Cnidaria: Scyphozoa: Rhizostomeae) - Ranko Gacesa; Adrian Jaimes-Becerra; Edgar Gamero-Mora; Steven Lynham; Gabriel Padilla; André C. Morandini; Antonio C. Marques; Paul F. Long (Journal of Experimental Marine Biology and Ecology, 2026)

Perennial forage-based fallows support long-term soil carbon and nutrient trajectories in smallholder rotations of the Peruvian Andes - Katherin Meza; Steven Vanek; Edgar Olivera; Jhon Huaraca; Maria Scurrah; Raul Ccanto; Steven J. Fonte (Agriculture, Ecosystems & Environment, 2025)

Global change drivers alter weed performance and threaten forage production in an Andean agroecosystem - Anna M. Visscher; Steven Vanek; Jhon Huaraca; Jamelith Mendoza; Raul Ccanto; Katherin Meza; Edgar Olivera; Steven J. Fonte (Agriculture, Ecosystems & Environment, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Influence of extruded soybean meal with different fat contents and varying oleic acid content on floating fish feed quality and composition - Danny B. Patiño; Ondulla T. Toomer; Thien C. Vu; Edgar O. Oviedo-Rondon; Rouf Mian; Mike Frinsko; Steven Hall; Ryan Kelly; Jason Mann; Michael Joseph (Animal Feed Science and Technology, 2024)

Lessons from long-term monitoring of tropical rock lobsters to support fisheries management - Éva Plagányi; Leo Dutra; Nicole Murphy; Steven Edgar; Kinam Salee; Roy Aijun Deng; Laura K. Blamey; Denham Parker; Stephanie Brodie (Fisheries Research, 2024)

Traditional soil fertility management ameliorates climate change impacts on traditional Andean crops within smallholder farming systems - Anna M. Visscher; Steven Vanek; Jhon Huaraca; Jamelith Mendoza; Raul Ccanto; Katherin Meza; Edgar Olivera; Maria Scurrah; Camilla Wellstein; Gianmaria Bonari; Stefan Zerbe; Steven J. Fonte (Science of The Total Environment, 2024)

Drivers of growth and establishment of the invasive plant Rumex acetosella within Andean fallow systems - Anna M. Visscher; Camilla Wellstein; Steven Vanek; Alessandro Bricca; Katherin Meza; Jhon Huaraca; Raul Ccanto; Edgar Olivera; José Loayza; Lionel Vigil; Samuel Palomino; Maria Scurrah; et al. (Agriculture, Ecosystems & Environment, 2023)

Tree-based land uses enhance the provision of ecosystem services in agricultural landscapes of the Peruvian highlands - Anna M. Visscher; Steven Vanek; Katherin Meza; Camilla Wellstein; Stefan Zerbe; Raul Ccanto; Edgar Olivera; Jhon Huaraca; Maria Scurrah; Steven J. Fonte (Agriculture, Ecosystems & Environment, 2023)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Indirect Impacts of COVID-19 on a Tropical Lobster Fishery’s Harvest Strategy and Supply Chain - Éva Plagányi; Roy Aijun Deng; Mark Tonks; Nicole Murphy; Sean Pascoe; Steven Edgar; Kinam Salee; Trevor Hutton; Laura Blamey; Leo Dutra (Frontiers in Marine Science, 2021)
The Torres Strait tropical rock lobster Panulirus ornatus (TRL) fishery is of immense social, cultural and economic importance to the region’s Indigenous fishers from both Australia and Papua New Guinea (PNG). During 2020, the COVID-19 pandemic indirectly impacted this fishery as well as a number of other fisheries reliant on international export markets. The TRL fishery is managed using an empirical (data-based) Harvest Control Rule (eHCR) to rapidly provide a recommended biological catch (RBC), based on catch, fishery-independent survey indices and catch-per-unit-effort (CPUE). Here, we summarize the impacts of COVID-19 on each of these critical data inputs and discuss whether the eHCR was considered adequately resilient to this unprecedented disruption to the system. Next, we use a quantitative supply chain index to analyze the impact of disruptions to the supply chain, and inform on potential adaptation strategies. The catch and CPUE data were impacted to varying degrees by external constraints influencing fishing effort, but the fishery-independent survey wasn’t affected and hence there remains an unbroken survey time-series for the fishery extending back to 1989. The eHCR was shown to be reasonably robust because it incorporates longer-term trends over a 5-year period, and accords substantially more weighting (80%) to the fishery-independent survey rather than CPUE data which can be affected by trade and other disruptions. Despite the eHCR not having been tested for scenarios such as a global pandemic, this robustness is a positive given the types of disruptions we will likely face in future climate. The weak links identified in the supply chain were the same as those previously highlighted as sensitive to climate change disruptions. Our supply chain analysis quantifies the impact on system resilience of alternative paths connecting producers to consumers and reinforces that supply chains may be particularly vulnerable to external disruptions if they are not sufficiently diverse.

Treatment with One Dose of Reltecimod is Superior to Two Doses in Mouse Models of Lethal Infection - Rotem Edgar; Margarite L. Tarrio; Greg Maislin; Feng Chiguang; Raymond Kaempfer; Alan Cross; Steven M. Opal; Anat Shirvan (International Journal of Peptide Research and Therapeutics, 2020)

Australia’s Long-Term Plankton Observations: The Integrated Marine Observing System National Reference Station Network - Ruth S. Eriksen; Claire H. Davies; Pru Bonham; Frank E. Coman; Steven Edgar; Felicity R. McEnnulty; David McLeod; Margaret J. Miller; Wayne Rochester; Anita Slotwinski; Mark L. Tonks; Julian Uribe-Palomino; et al. (Frontiers in Marine Science, 2019)

Annual Monitoring of US Timber Production: Rationale and Design - John W Coulston; James A Westfall; David N Wear; Christopher B Edgar; Steven P Prisley; Thomas B Treiman; Robert C Abt; W Brad Smith (Forest Science, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Over 75 years of zooplankton data from Australia - Claire H. Davies; Amelia J. Armstrong; Mark Baird; Frank Coman; Steven Edgar; Daniel Gaughan; Jack Greenwood; Felipe Gusmão; Natasha Henschke; J. Anthony Koslow; Sophie C. Leterme; A. David McKinnon; et al. (Ecology, 2014)
Zooplankton are the key trophic link between primary producers and fish in pelagic ecosystems. Historically, there are few zooplankton time series in Australia, with no data sets longer than two years prior to 2008. Here we compile 98 676 abundance records of more than 1000 zooplankton taxa from unpublished research cruises, student projects, published literature, and the recent Integrated Marine Observing System (IMOS). This data set covers the entire coastal and shelf region of Australia and dates back to 1938. Most records are for copepods, but there are also data for other taxa such as decapods, chaetognaths, thaliaceans, appendicularians, and cladocerans. Metadata are provided for each record, including dates, coordinates, and information on mesh size and sampling methods. To facilitate analysis across the multiple data sets, we have updated the species names according to the World Register of Marine Species (WoRMS) and converted units to abundance per cubic meter. These data will be valuable for studies of biodiversity, biogeography, impacts of climate change, and ecosystem health. We encourage researchers holding additional Australian zooplankton data to contact us and contribute their data to the data set so we can periodically publish updates.